ANALISIS PENGGUNAAN TEKNOLOGI APLIKASI AKUNTANSI PADA USAHA KECIL DAN MENENGAH (UKM) DI KABUPATEN BANYUMAS MELALUI PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Vieridho Rafif Raditya; Dona Primasari; Rini Widianingsih (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
This research focus on acceptance and using of accountant application technology on small-medium scale business with TAM approaches. The research is done to ninety eight small-medium scale business in Banyumas Regency with purposive sampling as sampling method. This research use quantitative survey to collect data. The research data is a primary data with questionnaire collective method. The collected data were analyzed using SmartPLS 3.0. The result of this study indicate that the perceived ease of use significantly impacts perceived usefulness and attitude toward using of accountant application technology, perceived usefulness significantly impacts attitude toward using of accountant application technology, attitude toward using significantly impacts behavioral intention of accountant application technology, and behavioral intention significantly impacts actual system using of accountant application technology.